Role of tubular cell-derived exosomes in renal ischemia reperfusion injury - Jin-zhu Huang; Yan-zi Zhang; Cui-yu Yang; Ai-sha Zhang; Xiao-lu Sui; Yun-peng Xu; Ting-fei Xie; Ji-hong Chen (Editorial Department of Journal of Clinical Nephrology, 2024)
Renal ischemia reperfusion injury refers to a pathophysiological phenomenon that aggravates the degree of renal injury due to the restoration of blood supply after transient ischemia of renal tissue. It has been found that renal tubular cell-derived exosomes alleviate renal ischemia reperfusion injury through anti-inflammatory, antioxidant, inhibition of apoptosis, promotion of tissue regeneration and activation of autophagy . This review will discuss the protective effect of tubular cell-derived exosomes on renal ischemia reperfusion injury, in order to provide a theoretical basis for the clinical diagnosis, treatment and early prevention of renal ischemia reperfusion injury.